Differential gas exchange and soil microclimate dynamics under biodegradable plastic, polyethylene, and paper mulches - Sintim, Henry Y.; Shahzad, Khurram; Bary, Andy I.; Collins, Douglas P.; Myhre, Elizabeth A.; Flury, Markus (Italian Journal of Agronomy, 2022)
Biodegradable plastic mulch is potentially a suitable alternative to conventional polyethylene mulch because of the limited disposal options of the latter. However, biodegradable plastic mulch must perform better or comparably to polyethylene mulch to be widely adopted. Gas exchange and soil microclimate are important factors impacted by the use of plastic mulch, which in turn have implications on crop productivity. A controlled-environment study was established in a greenhouse to assess gas exchange and soil microclimate dynamics under biodegradable plastic, polyethylene, and paper mulches with and without planting holes, as well as the impact of the mulches on the growth of sweet corn (Zea mays). A no-mulch condition was included as control. In addition, we monitored CO2 concentrations in the vicinity of planting holes (chimney effect) in a greenhouse and agricultural field conditions under sweet corn production. The plastic mulches (both biodegradable plastic and polyethylene mulches) decreased the soil O2 concentration to a minimum of 181-183 mmol mol–1, and when compared to the no-mulch, the plastic mulches reduced water loss within 50 days by 35-68 mm. The paper mulch inhibited light penetration more than did the plastic mulches. There was an increase in the CO2 concentration at 2.5 cm above the planting holes in the plastic mulches compared to that under the no-mulch. The plastic mulches (both biodegradable plastic and polyethylene mulches) decreased the soil growth of sweet corn, possibly, because the canopy height of sweet corn was more than 15 cm within a few days after planting. Overall, the plastic mulches did not reduce O2 concentration below 100 mmol mol–1, the minimum level at which plant growth becomes impaired. Also, the often reported improved growth of sweet corn from plastic mulching could be attributable to other factors, such as weed control, reduced water loss, and early season soil warming, rather than elevated CO2 concentrations and fluxes in the vicinity of planting holes. Highlights - Gas exchange and soil microclimate dynamics under biodegradable plastic, polyethylene, and paper mulches were assessed. - Elevated CO2 levels were observed near planting holes of plastic mulches (both biodegradable and polyethylene). - The plastic mulches inhibited O2 exchange, but not to a level that could impair plant growth. - Polyethylene mulch conserved soil water better than biodegradable plastic and paper mulches.